A comparative study of circularity of artefact detecting circle using CMM and form tester with different filters. (2020) - Raghu, S.; Mamatha, T.G.; Pali, H.S.; Sharma, Rina; Vimal, J.R.; Kumar, Vinod
Abstract: This paper presents a study of circularity of the different workpiece using CMM for smooth functioning of manufactured parts. The present work to study of roundness of different artefact using different algorithm and filters. For the present study have been conducted on RA-2200CNC form tester and LEGEX 9106 CMM by selecting two filters and four types of algorithm with different range of spectral wave numbers in terms of undulations per revolution (UPR) and fitting software techniques. Instrument data set help the designer and operator to satisfy the best fit for roundness in nano scale metrology.